The pulsed microwave damage trend of a bipolar transistor as a function of pulse parameters - 马振洋 柴常春 任兴荣 杨银堂 赵颖博 乔丽萍 (Chinese physics B, 2013)
In the present paper we conduct a theoretical study of the thermal accumulation effect of a typical bipolar transistor caused by high power pulsed microwaves（HPMs）,and investigate the thermal accumulation effect as a function of pulse repetition frequency（PRF） and duty cycle.A study of the damage mechanism of the device is carried out from the variation analysis of the distribution of the electric field and the current density.The result shows that the accumulation temperature increases with PRF increasing and the threshold for the transistor is about 2 kHz.The response of the peak temperature induced by the injected single pulses indicates that the falling time is much longer than the rising time.Adopting the fitting method,the relationship between the peak temperature and the time during the rising edge and that between the peak temperature and the time during the falling edge are obtained.Moreover,the accumulation temperature decreases with duty cycle increasing for a certain mean power.